51.3k views
1 vote
2x – (5 – x) = 13 + x solve step by step please

User Tadatuta
by
4.5k points

2 Answers

2 votes

Answer:


\boxed {x = 9}

Explanation:

Solve for the value of
x:


2x - (5 - x) = 13 + x

-To find the opposite of
5 - x, find the opposite of each term:


2x - (5 - x) = 13 + x


2x - 5 + x = 13 + x

-Combine like terms:


2x - 5 + x = 13 + x


3x - 5 = 13 + x

-Take
x and subtract it from
3x:


3x - 5 - x = 13 + x - x


2x - 5 = 13

-Add
5 on both sides:


2x - 5 + 5 = 13 + 5


2x = 18

-Divide both sides by
2:


(2x)/(2) = (18)/(2)


\boxed {x = 9}

So, therefore, the value of
x is
9.

User Katie Astrauskas
by
4.9k points
6 votes

Answer:

9

Explanation:

Step 1:

2x - ( 5 - x ) = 13 + x Equation

Step 2:

2x - 5 + x = 13 + x Open the parenthises

Step 3:

3x - 5 = 13 + x Add

Step 4:

3x = 18 + x Add 5 on both sides

Step 5:

2x = 18 Subtract x on both sides

Step 6:

18 ÷ 2 Divide

Answer:

x = 9

Hope This Helps :)

User Raphael Jeger
by
4.6k points